HEPATIC HYDROTHORAX WITHOUT ASCITES: A DIAGNOSTIC AND MANAGEMENT CHALLENGE - Malick, Maria; Shahid, Wajeeha; Latif, Anum; Zarafshan Zubair; Zaidi, Syeda Moazzama (Journal of Ayub Medical College Abbottabad, 2024)
Hepatic hydrothorax refers to the presence of a pleural effusion (usually >500 mL) in a patient with cirrhosis who does not have other reasons to have a pleural effusion (e.g., cardiac, pulmonary, or pleural disease). Hepatic hydrothorax occurs in approximately 5-6% of patients with cirrhosis. It results from the ascitic fluid draining into the pleural cavity through the diaphragmatic defects. The presentation of patients with hepatic hydrothorax includes chest pain, hypoxemia, cough, shortness of breath and fatigue. The atypical feature, in this case, is the presence of hepatic hydrothorax in a patient with chronic liver disease without ascites. The management of hepatic hydrothorax is difficult. The initial treatment should be a low-salt diet plus diuretics. The best diuretic regimen is probably the combination of furosemide and spironolactone. However, about 25% of patients are refractory to this regimen, and additional therapy is indicated. This patient underwent thoracentesis, however, considering the re-accumulation of fluid, a pigtail catheter was placed which drained up to 8 liters of fluid.